The Impact of Acculturation and Religiosity on Cultural Alignment: Terror Management Mechanisms among Muslim Americans - Goheer, Farah Taha; Doherty, Jaclyn K.; Sneed, Joel R.; Brumbaugh, Claudia (Journal of Ethnic and Cultural Studies, 2025)
The current investigation examined terror management defenses employed by Muslim Americans and moderating effects of acculturation and religiosity. Associations between death salience and worldview defense were predicted to vary according to acculturation and religious commitment. Study 1 measured acculturation and reactions to traditional or modern Muslim targets. Study 2 assessed religiosity and acculturation effects on reactions to a worldview-threatening essay. Against expectations, heightened mortality salience did not result in the typical increase in worldview defense, nor was there a moderating effect of acculturation or religiosity. Furthermore, the relationship between mortality salience and worldview defense was not moderated by acculturation or religiosity. Thus, when confronted with existential threats, Muslim Americans may not separate their religious and secular worldviews to defend against mortality concerns. Although the pattern of results was unexpected, this study provides novel information suggesting that Muslim Americans may handle mortality salience in ways not yet revealed by previous TMT studies.